An unusual case of dental infection by Pseudomonas aeruginosa causing a brain abscess: case report - Pereira, R. S.; Bonardi, J. P. [UNESP]; Ferreira, A. C.D.; Latini, G. L. (Wiley, 2017)
A brain abscess may result when dental infection reaches the brain through contiguous anatomic cavities such as the maxillary sinus, the ethmoid sinus and the orbital cavity. It is an important complication and should be treated aggressively. Such treatment would include the excision of the etiological factor, drainage and adjuvant antibiotic therapy. The present case concerns a 23 year old woman who presented at the General Hospital of Nova Iguaçu with complaints of pain in the right side of the face and was diagnosed with acute sinusitis. Antibiotics and analgesics were prescribed to treat the disease. However, after 10 days, she returned to the emergency room, presenting with proptosis of the right eyeball, subconjunctival haemorrhage, ophthalmoplegia and intense pain in the right orbit, in addition to headaches. After computed tomography was performed, she was diagnosed with a brain abscess in the frontal lobe with the involvement of the maxillary right first molar, the maxillary sinus, the ethmoid sinus and the orbital cavity. With culturing of the secretion, the growth of Pseudomonas aeruginosa colonies was evident. Treatment consisted of a craniotomy to drain the brain abscess, a Caldwell–Luc procedure to drain the right maxillary sinus, dental extraction and aggressive antibiotic therapy. After 6 weeks, the patient was discharged with no neurological sequelae.
Keywords: Brain infection; dental infection; maxillary sinus infection; maxillary sinusitis; Pseudomonas aeruginosa